Modification of polyetheretherketone implants: From enhancing bone integration to enabling multi-modal therapeutics. (15th July 2021) - He, Miaomiao; Huang, Yong; Xu, Huan; Feng, Ganjun; Liu, Limin; Li, Yubao; Sun, Dan; Zhang, Li
Abstract: Polyetheretherketone (PEEK) is a popular thermoplastic material widely used in engineering applications due to its favorable mechanical properties and stability at high temperatures. With the first implantable grade PEEK being commercialized in 1990s, the use of PEEK has since grown exponentially in the biomedical field and has rapidly transformed a large section of the medical devices landscape. Nowadays, PEEK is a standard biomaterial used across a wide range of implant applications, however, its bioinertness remains a limitation for bone repair applications. The increasing demand for enhanced treatment efficacy/improved patient quality of life, calls for next-generation implants that can offer fast bone integration as well as other desirable therapeutic functions. As such, modification of PEEK implants has progressively shifted from offering desirable mechanical properties, enhancing bioactivity/fast osteointegration, to more recently, tackling post-surgery bacterial infection/biofilm formation, modulation of inflammation and management of bone cancers. Such progress is also accompanied by the evolution of the PEEK manufacturing technologies, to meet the ever increasing demand for more patient specific devices. However, no review has comprehensively covered the recently engaged application areas to date. This paper provides an up-to-date review on the development of PEEK-based biomedical devices in the past 10 years, with particularly focus on modifying PEEK for multi-modal therapeutics. The aim is to provide the peers with a timely update, which may guide and inspire the research and development of next generation PEEK-based healthcare products. Statement of significance: Significant progress has been made in PEEK processing and modification techniques in the past decades, which greatly contributed to its wide applications in the biomedical field. Despite the high volume of published literature on PEEK implant related research, there is a lack of review on its emerging applications in multi-modal therapeutics, which involve bone regeneration, anti-bacteria/anti-inflammation, and cancer inhibition, etc. This timely review covers the state-of-the-art in these exciting areas and provides the important guidance for next generation PEEK based biomedical device research and development. Graphical abstract: Image, graphical abstract